Securing wireless networks against eavesdropping using smart antennas - Lakshmanan, Sriram (Georgia Institute of Technology, 2009)
In this work, we focus on securing communication over wireless data networks from malicious eavesdroppers, using smart antennas. While conventional cryptography based approaches focus on hiding the meaning of the information being communicated from the eavesdropper, we consider a complimentary class of strategies that limit knowledge of the existence of the information from the eavesdropper. We profile the performance achievable using simple beamforming strategies using a newly defined metric called exposure region. We then present three strategies within the context of an approach called 'virtual arrays of physical arrays' to significantly improve the exposure region performance of a wireless LAN environment. Using simulations, analysis, and field experiments, we validate and evaluate the proposed strategies.